Gut Microbiome Biomarkers and Functional Diversity Within an Amazonian Semi-Nomadic Hunter–Gatherer Group - Conteville, Liliane Costa; Oliveira-Ferreira, Joseli; Vicente, Ana Carolina Paulo (Frontiers in Microbiology, 2019)
Human groups that still maintain traditional modes of subsistence (hunter-gatherers and rural agriculturalists) represent human groups non-impacted by urban-industrialized lifestyles, and therefore their gut microbiome provides the basis for understanding the human microbiome evolution and its association with human health and disease. Here, based on shotgun metagenomic data, we characterized the gut microbiome of the Yanomami from Brazil and compared taxonomically and functionally with the Yanomami from Venezuela, with other traditional groups from the Amazon and an urban-industrialized group. The Yanomami is the largest semi-nomadic hunter-gatherer group of the Americas, exploring different niches of the Amazon rainforest in Brazil and Venezuela. Taxonomic biomarkers were identified to each South American traditional group studied, including each Yanomami group. Broader levels of functional categories poorly discriminated the traditional and urban-industrialized groups, but the stratification of these categories revealed clear segregation of these groups. The Yanomami/Brazil gut microbiome presented unique functional features, such as a higher abundance of gene families involved in regulation/cell signaling, motility/chemotaxis, and virulence, contrasting with the gut microbiomes from the Yanomami/Venezuela and the other groups. Our study revealed biomarkers, taxonomic and functional features that distinguished the gut microbiome of Yanomami/Brazil and Yanomami/Venezuela individuals, despite their shared lifestyle and cultural and genetic background. These differences may be a reflection of the environmental and seasonal diversity of the niches they explore. And overall, their microbiome profiles are shared with South American and African traditional groups, probably due to their lifestyle. The unique features identified within the Yanomami highlight the bias imposed by underrepresented sampling, and factors such as variations over space and time (seasonality) that impact, mainly, the hunter-gatherers.